The lost king : the search for Richard III - Langley, Philippa, 1962-; Jones, Michael K. (St. Martin's Press, 2023)
The mystery of who Richard III really was has fascinated historians for centuries. In 2013, the remains of a man with a curving spine, who possible was killed in battle, were discovered underneath the paving of a parking lot in Leicester, England. Langley led the team of who uncovered the remains, certain that she had found the bones of the monarch. DNA verification later confirmed that the skeleton was, indeed, that of King Richard III. Langley and Jones provides a portrait of the last Plantagenet monarch-- and the story of the archaeological dig that finally brought him into the light of day.